1994
DOI: 10.1111/j.1432-1033.1994.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Denaturation and Aggregation of β‐Lactoglobulin

Abstract: A quantitatively correct kinetic model for the temperature-induced denaturation and aggregation of P-lactoglobulin is presented. The model recognizes an initiation, a propagation and a termination step by analogy with polymer radical chemistry. The decrease in native P-lactoglobulin is predicted to follow order 312, in agreement with experimental results. The size of the protein polymer particles is predicted to be proportional to the square root of the initial P-lactoglobulin concentration. The scattered ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
322
7
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(366 citation statements)
references
References 12 publications
35
322
7
2
Order By: Relevance
“…2d. A sigmoidal curve, indicative of a cooperative mechanism, cannot be expected under these conditions to be due to an additional irreversible association that can take place at high temperature and involves intermolecular chemical reactions through the formation of new disulphide bonds among denaturated molecules [14,18,19]. This is confirmed by the sudden decrease of ellipticity on going from 70 to 90°C.…”
Section: Studiessupporting
confidence: 57%
See 1 more Smart Citation
“…2d. A sigmoidal curve, indicative of a cooperative mechanism, cannot be expected under these conditions to be due to an additional irreversible association that can take place at high temperature and involves intermolecular chemical reactions through the formation of new disulphide bonds among denaturated molecules [14,18,19]. This is confirmed by the sudden decrease of ellipticity on going from 70 to 90°C.…”
Section: Studiessupporting
confidence: 57%
“…The association behaviour of [3-LG is largely influenced by pH changes: the two most common variants of bovine 13-LG, [3-LG-A and -B (which differ in two amino acids), are in a monomer-dimer equilibrium at pH 3.0 and appear to form higher aggregates above pH 3.5 [14]. Since of these two forms it is only the monomer that can be amenable to a detailed NMR study, we undertook a search for the conditions under which the equilibrium is completely shifted towards the formation of the monomer.…”
Section: Introductionmentioning
confidence: 99%
“…A mechanism for -lg denaturation under conditions similar to those used in this study has been proposed previously (Roefs & de Kruif, 1994). However, the rapid denaturation of BSA during the initial stages of heat denaturation in this study could alter the mechanism of the protein aggregation.…”
Section: Discussionmentioning
confidence: 69%
“…For instance, it was reported that intermolecular S-S bridge formation depends on the concentration of -lactoglobulin at temperature below 75 C, but S-S bridge formation does not depend on the concentration of -lactoglobulin at temperature higher than 75 C (Iametti et al, 1996). Other researchers (Roefs and De Kruif, 1994;Hoffmann and vanMil, 1997) also found same results upon addition of -lactoglobulin that the average size of the protein complexes (S-S bridge formation) was increased with increasing the concentration of -lactoglobulin from 10 to 50 mg/mL during heating at temperature up to 65 C.…”
Section: Milk Compositionmentioning
confidence: 99%